KAJIAN POTENSI TERJADINYA TUNTUTAN KONTRAKTOR PELAKSANA TERHADAP PENGGUNA JASA (OWNER) PADA PROYEK - Zakia Zakia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
In the world of construction, pengendaliaan time, cost and quality are very important for achieving the ultimate goal of the project. Demands are filed compensation requests of the executor of the service providers. Charges could result in failure to achieve the ultimate goal of a project that has been planned in advance. Besides the losses incurred can affect the work or product. Those who feel aggrieved can file charges to include any losses experienced and an explanation of the rights that have been violated. The problem is to know which factors are most likely to cause the occurrence of claims from the contractor of the project owner (owner). The purpose of this research is to mengindentifikas factors that potentially cause the demands of service providers (contractors Executor) to service users. Based on data analysis, it is found 17 items of questions from 32 questions otherwise valid Corrected Item Total Correlation values> 0.3, while the other 15 question items is invalid because the value of Corrected Item Total Correlation <0.3. Analysis of reliability can be seen that the value cronbach'alpha if item deleted> 0.60, meaning that 32 respondents in the 32 item questionnaire that question is accurate, stable and consistent. Factors differences in field conditions is a factor that causes the highest demands. Keywords: potential, the demands of the contractor.